2014
DOI: 10.1051/0004-6361/201423498
|View full text |Cite
|
Sign up to set email alerts
|

On helium-dominated stellar evolution: the mysterious role of the O(He)-type stars

Abstract: Context. About a quarter of all post-asymptotic giant branch (AGB) stars are hydrogen-deficient. Stellar evolutionary models explain the carbon-dominated H-deficient stars by a (very) late thermal pulse scenario where the hydrogen-rich envelope is mixed with the helium-rich intershell layer. Depending on the particular time at which the final flash occurs, the entire hydrogen envelope may be burned. In contrast, helium-dominated post-AGB stars and their evolution are not yet understood. Aims. A small group of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 45 publications
4
86
1
2
Order By: Relevance
“…While the mass of SDSS J1728 is relatively high, that of KPD 0005+5106 appears too low, suggesting its origin is either one of the rare He+He WD mergers or a He+CO WD merger where the He-WD had a significantly lower mass than the lower 0.3 M limit postulated by Zhang et al (2014). But we do note that the masses of the two stars were derived with VLTP post-AGB tracks, while post-merger tracks yield masses that are systematically higher by about 0.1−0.2 M (Reindl et al 2014).…”
Section: Summary and Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…While the mass of SDSS J1728 is relatively high, that of KPD 0005+5106 appears too low, suggesting its origin is either one of the rare He+He WD mergers or a He+CO WD merger where the He-WD had a significantly lower mass than the lower 0.3 M limit postulated by Zhang et al (2014). But we do note that the masses of the two stars were derived with VLTP post-AGB tracks, while post-merger tracks yield masses that are systematically higher by about 0.1−0.2 M (Reindl et al 2014).…”
Section: Summary and Discussioncontrasting
confidence: 58%
“…The element abundances are summarized in Table 4 and displayed in Fig. 7, together with results for RCB and EHe stars (from Jeffery et al 2011, and references Currently, ten objects were assigned to the group of O(He) stars (Reindl et al 2014;Werner et al 2014;De Marco et al 2015). They cover a parameter range of T eff = 80 000−195 000 K and log g = 5.0−6.7.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the presence of spectral lines originating from trans-iron elements, such as Ge, Ga, As, Sn, and Pb, in the spectra of hot subdwarf stars as well as in those of a few hot white dwarfs (O'Toole 2004;Naslim et al 2011;Werner et al 2012;Rauch et al 2015, and references therein), it is possible that the opacity of such elements constitutes a part of the missing opacity. Reindl & Rauch (2015) also showed that Ne in solar abundances can lead to a strong change in the temperature structure of the atmosphere in a 100 kK model (see also Reindl et al 2014). However, it seems slightly odd that such missing opacities would significantly affect the Balmer and helium optical lines, while the UV lines can be accounted for very well without the induced change in the atmospheric structure.…”
Section: Discussionmentioning
confidence: 97%
“…None of the recent late TP scenarios predicts the observed surface compositions of PB 8, IC 4663, and Abell 48. It was speculated whether these objects belong to an alternative evolutionary sequence [WN] → O(He) (Miszalski et al 2012, Werner 2012 or that [WN] stars are O(He) stars with higher masses (Reindl et al 2014), evolving from RCB or sdO(He) stars, which might be merger products of non-DA WDs. However, the merger scenario seems to be rather unlikely due to the long timescales involved, which are incompatible with the observed low ages of the PNe of the [WN] stars.…”
Section: Evolutionary Statusmentioning
confidence: 99%